Nutritional management and weight changes during hospitalization of Brazilian infants with diarrhoea: Primary reliance on oral feeding or continuous nasogastric drip with locally made, modulated minced chicken formula - Maffei, H. V L; Niura, N. A M; Padula, M. B.; Annicchino, G. P.; Ferrari, G. F.; Goldberg, T. B L (Oxford University Press (OUP), 1990)
The nutritional management of infants admitted with diarrhoea to the University Hospital of Botucatu includes a change from bolus feeding of a modulated minced-chicken formula to a continuous nasogastric drip (NGD) feeding, whenever the required calorie intake is not achieved or the diarrhoea does not subside. To evaluate this approach, the clinical course and weight changes of 63 children, aged 1-20 months, were reviewed; most (81 per cent) were below the third percentile for weight at admission and 76 per cent had a total duration of diarrhoea ≥10 days. Associated infections, mainly systemic, were present at or after admission in 70 per cent of them. Twenty-five survivors needed nutritional support (NS), predominantly NGD, for a median duration of 30 per cent of their admission time, and were compared to 31 survivors managed without NS. Those who necessitated NS lost weight for a significantly longer median time (12x4 days, p<0.005), but their total weight loss was similar (5x4 per cent) as well as diarrhoea's duration (8x7 days). There was a tendency for a longer hospitalization (21x16 days 0.05<P<0.10) and a longer span to begin weight gain after diarrhoea's end for the group with NS (p<0.05), but subsequent growth quotient and daily weight gain during admission were similar for both groups. Both groups of survivors received similar amounts of energy, although the initial increase was delayed for those who needed the NGD. Seven infants (11 per cent) died, most of overwhelming infection, and presented a high total weight loss, albeit receiving NS for 71 per cent of their admission's time. It was concluded that feeding diarrhoeic infants with a NGD when necessary, possibly prevented a greater nutritional insult for the survivors. The NGD can be safely employed and should be valued, provided weight losses are carefully monitored in order to detect infants at highest risk.
Keywords: brazil; chicken; diarrhea; human; infant; major clinical study; nasogastric tube; nutrition; preschool child; weight reduction; Brazil; Diarrhea, Infantile; Enteral Nutrition; Food, Formulated; Human; Infant; Infant Food; Weight Gain; Weight Loss